Pengaruh Profitabilitas, Leverage, dan Likuiditas terhadap Nilai Perusahaan pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia - Mulyadi, Rahmad; Afriyeni, Afriyeni (ARZUSIN, 2025)
Enhancing firm value is a primary objective for every business entity as it reflects sound financial performance and attracts investor interest. However, understanding the internal financial factors that consistently influence firm value, particularly in the telecommunications sector, remains limited. This study aims to analyze and examine the effect of profitability, leverage, and liquidity on firm value in the telecommunications sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative method was employed with descriptive and associative approaches, using secondary data from annual financial reports obtained from the official IDX website. The research sample was selected through purposive sampling, involving 20 companies over four years, resulting in 80 observation units. Data analysis was conducted using multiple linear regression with the aid of SPSS version 25 software. The results show that profitability has a positive and significant effect on firm value, leverage has a significant negative effect, while liquidity does not have a significant effect. These findings suggest that in the telecommunications sector, profitability and capital structure play a more crucial role in enhancing firm value compared to liquidity. The implications point to the need for management to focus more on strategies to increase profitability and manage capital structure to maximize firm value.